Preparation of altrenogest soft capsules and their bioequivalence in gilts - Xu, Jinxia; Ling, Lifang; Lan, Yanhua; Yuan, Ye; Ran, Long; Jiang, Jiaxin; Huang, Xianhui (Frontiers in Veterinary Science, 2024)
IntroductionAltrenogest (ALT) is widely used to regulate the estrous cycle of sows and mares; however, currently used oral solutions of ALT are deficient in terms of dose accuracy and stability during use. To resolve these problems, we aimed to prepare softgel capsules of ALT with a unit dose equal to the clinically administered dose.MethodThe shell of the softgel capsule was mainly composed of gelatin and glycerol, with titanium dioxide and red iron oxide as masking agents. Using the shake flask method, the contents were screened for ethyl acetate as a lipophilic solubilizing carrier based on soya bean oil. The contents were automatically filled and compressed into softgel capsules by a softgel capsule machine. The quality of the prepared softgel capsules was evaluated through a drug content test, an in vitro release test, and stability studies. Furthermore, bioequivalence studies were conducted with atrenogest oral solution.ResultsThe content is an ALT concentration of 2% oil solution and the specification of the softgel is 20 mg/capsule. In in vitro dissolution experiments, the softgel capsules were rapidly disintegrated and released in three different pH buffers, with a cumulative release rate of nearly 100% at 1 h. The softgel capsules were stable at high temperature and under strong light for 10 days, and the concentration of ALT was >99% in the 6-month accelerated and long-term tests. In the bioequivalence study, Tmax of the softgel capsules was 2.20 ± 0.77 h, t1/2 was 6.36 ± 1.74 h, and Cmax was 64.65 ± 20.69 ng/ml. The main pharmacokinetic parameters Tmax, Cmax, AUC0−t, and AUC0−∞, did not differ significantly between the softgel capsules and the commercially available ALT oral solution (P > 0.05), and bioequivalence was demonstrated within the 90% confidence interval.ConclusionThe prepared softgel capsules have the advantages of higher content, ease of use with accurate dosing, good stability, and equivalence to ALT oral solution, implying that our softgels are ready for clinical use.